DOP040 Five-year colectomy data from the observational postmarketing ulcerative colitis study, a European registry for adults with ulcerative colitis treated with originator infliximab or conventional therapy. (16th January 2018) - Panés, J; Lindsay, J O; Teich, N; Lindgren, S; Colombel, J -F; Cornillie, F; Ann Flynn, H; Huyck, S; Stryszak, P; Yao, R; Philip, G; Reinisch, W
Abstract: Background: The Observational Postmarketing Ulcerative colitis Study (OPUS) registry was conducted to collect long-term (5 years) real-world clinical practice safety data in patients with moderate to severe ulcerative colitis (UC) treated with originator infliximab (IFX) and to compare this safety profile to that of UC patients treated with conventional therapies (ConvRx). Methods: The OPUS registry was a prospective, non-randomised, observational study that followed patients with UC (in routine practice across 14 European countries) who were enrolled to receive treatment with either IFX or ConvRx, as determined by their treating physician. At any time during the study, the patient's therapy could be changed to any other UC therapy, based on the physician's clinical judgment. In the intention-to-treat main analysis, Cox proportional hazards models adjusting for baseline covariates of disease severity, smoking history, and other UC medications were used to compare time to colectomy for the IFX and ConvRx groups. In a separate secondary analysis, colectomy incidence rates were examined using an exposure-adjusted approach based on the timing of exposure to IFX, with IFX exposure time being defined as <90 days after the most recent IFX dose. Results: Data for 2239 patients were available: 1180 patients enrolled to ConvRx (including 296 patients who switched to IFX during follow-up) and 1059 patients enrolled to IFX. Patients selected by their physicians to start IFX had more severe disease at baseline (eg, by partial Mayo score) than those selected for ConvRx. A total of 222 patients (9.9% of registry cohort) had colectomy during 5 years of follow-up. In time-to-event analyses, enrolment in the IFX group was associated with a higher risk of colectomy (hazard ratio = 3.12; 95% CI [2.25, 4.34]; p < 0.001) compared with enrolment in the ConvRx group. But after controlling for exposure to IFX (Table), the incidence rates of colectomy were similar when exposed (<90days of dosing with IFX), 27.0/1000 PY, as when not exposed (≥90 days after the most recent dose), 22.7/1000 PY. Within the IFX registry group, 97 of the colectomies occurred during the (up to) 5 years of follow-up when not exposed to IFX, with incidence rate = 48.9/1000PY. Conclusions: Although colectomy was reported at a higher rate in the IFX registry group compared with the ConvRx registry group, the IFX registry group had more severe disease at baseline and most of the colectomies in this group occurred after patients had been off IFX for at least 90 days.